Islamic Model of Political Leadership as a Potential Way to Start Negotiations Aimed at Resolving the Israeli-Palestinian Conflict - Ryzhov, Igor V.; Rogozhina, Evgeniya M.; Abidulin, Alim M.; Savin, Ilya S.; Borodina, Maria Yu. (Journal of History Culture and Art Research, 2019)
The paper reviews the issue of the creation of a fundamentally new innovative model of negotiation process focused on settling the Israeli-Palestinian conflict. In the author’s opinion, political leadership factor that is typical for the Arab-Israeli world is instrumental in providing a conceptual framework for peace talks between Israel and Palestine in the context of globalization. The article focuses on the peculiarities of the Islamic model of political or, to be more precise, religious and political leadership and how it can be implemented to give a new impetus to the currently bogged down Israeli-Palestinian peace talks. The author argues that is impossible to achieve any tangible regional treaty because not all the arrangements concerning Palestine have a legitimate character from the point of view of both the Palestinians and the people of other Muslim countries in the world. Therefore, in the author’s opinion, without using such an innovative model of the negotiation process it will be principally impossible to achieve a final settlement of the Israeli-Palestinian conflict.